Deiksis waktu dalam cerpen “Ketika Laut Marah” karya Widya Suwarna: Tinjauan pragmatik - Sirait, Nurul Aulia (Maliki Interdisciplinary Journal, 2024)
This study describes the time deixis in the short story “When the sea is Angry” using a pragmatic approach. Pragmatics is the study of context and meaning in speech (writer) and requires interpretation from the listener (reader). This study requires interpretation of what is meant in the context and how the influence process has been conveyed. One branch of pragmatic studies is deixis. Deixis according to buhler’s view (2011:67), is divided into three parts, namely the first is persona deixis, the persona is related to people and objects, then the next deixis is space deixis which is related to time, then the last is temporal deixis which is related to time. Based on the results of the data analysis, it can be concluded that the time deixis in the short story “When the sea is Angry” is : (a) Deixis that indicates the time that has occurred, namely: it has been four days, at night, like yesterday, (b) Deixis that indicates the time that is currently occurring, namely: now is the fifth day, early in the morning< if today, at noon< (c) Deixis that indicates the time that will occur, namely: tomorrow, this afternoon, this evening.